The I-learning model improvement on writing digital-based scientific papers for students of faculty of letters universitas Muslim Indonesia - Akidah, Ihramsari; Mantasiah, Mantasiah; Hamsa, Akmal; Padhil, Ahmad (Edelweiss Applied Science and Technology, 2024)
The time-consuming and often fraught writing process can be draining and demotivate writers from completing their writing well. By overcoming these problems, writers can improve the effectiveness and quality of their scientific writing. The problem limitation in this study, how is the development of the I-Learn model on digital-based scientific writing for students of the Faculty of Letters UMI? In connection with the statement of the problem, the purpose of this study is to produce a development of the I-Learn model of learning scientific writing for students of the Faculty of Letters, UMI. Development research or Research and Development (R&D) is a process or steps to develop a new product, or improve existing products, which can be accounted for. The variable as the focus of review in this study is the I-Learn learning model on digital-based scientific writing. The development of the I-Learn model in learning to write digital-based scientific papers was carried out by following the ADDIE development model. The ADDIE development process is carried out through five stages, namely 1) Analysis (Analyze); 2) Design; 3) Development; 4) Implement; and 5) Evaluate. Analysis is used to obtain an initial description of the learning conditions for digital-based scientific writing for students of the Faculty of Letters, Universitas Muslim Indonesia. This analysis stage is carried out using a qualitative research method of literature study type. The research data is qualitative data obtained from document analysis, interviews, and observations. The research data can be divided into four parts, namely: (1) curriculum analysis, (2) Learning PlanAnalysis, (3) teaching material analysis, and (4) interview and learning process analysis.